Fitness implications of seasonal climate variation in Columbian ground squirrels. Issue 16 (16th July 2016) - Dobson, F. Stephen; Lane, Jeffrey E.; Low, Matthew; Murie, Jan O.
Abstract : Seasonal climate variables influence fitness in Columbian ground squirrels. Snow melt‐off in spring has gotten later in the past 21 years, and early summer rainfall has become sparser. Both climate variables had significant negative influences on annual fitness, although the latter was a slightly stronger influence. Abstract: The influence of climate change on the fitness of wild populations is often studied in the context of the spring onset of the reproductive season. This focus is relevant for climate influences on reproductive success, but neglects other fitness‐relevant periods (e.g., autumn preparation for overwintering). We examined variation in climate variables (temperature, rainfall, snowfall, and snowpack) across the full annual cycle of Columbian ground squirrels ( Urocitellus columbianus ) for 21 years. We investigated seasonal climate variables that were associated with fitness variables, climate variables that exhibited directional changes across the study period, and finally observed declines in fitness (−0.03 units/year; total decline = 37%) that were associated with directional changes in climate variables. Annual fitness of adult female ground squirrels was positively associated with spring temperature ( r = 0.69) and early summer rainfall ( r = 0.56) and negatively associated with spring snow conditions ( r = −0.44 to −0.66). Across the 21 years, spring snowmelt has become significantly delayed ( r = 0.48) and summer rainfall became significantly reduced ( r = −0.53). Using a standardized partial regression model, we found that directional changes in the timing of spring snowmelt and early summer rainfall (i.e., progressively drier summers) had moderate influences on annual fitness, with the latter statistically significant ( ρ = −0.314 and 0.437, respectively). The summer period corresponds to prehibernation fattening of young and adult ground squirrels. Had we focused on a single point in time (viz. the onset of the breeding season), we would have underestimated the influences of climate change on our population. Rather, we obtained a comprehensive understanding of the influences of climate change on individual fitness by investigating the full lifecycle.